10 Questions for Professor David Crystal - David Crystal; Thomas Tinnefeld (Journal of Linguistics and Language Teaching)
The world-renowned British linguist, Professor David Crystal, kindly provided insightful responses to ten pertinent questions within his field of expertise for JLLT. His discourse encompasses a broad range of topics, including the practical implications of linguistics, the internet and online communication platforms, language death, English as a global lingua franca, language-related challenges in education, language play and creativity, the importance of Shakespeare for our present lives, and linguistics as an interdisciplinary science, to name but a few. Professor Crystal’s profound insights underscore the significance of applied linguistics and the heightened awareness it can foster in various contexts where we use our language(s), both in personal and professional spheres.